Endogenous Output in an Aggregate Model of the Labor Market - Quandt, Richard E.; Rosen, Harvey S. (The Review of Economics and Statistics, 1989)
A common feature to most aggregative studies of the labor market is a marginal productivity expression in which the quantity of labor appears on the left hand side of the equation, and the right hand side includes the real wage and output. A number of researchers have cautioned that if the output variable is treated as exogenous, serious econometric difficulties may result. However, the assumption that output is exogenous has not been tested. In this paper, we estimate an equilibrium model of the labor market, and use it to test the assumption of output exogeneity. We find that the assumption that output is exogenous cannot be rejected by the data.